Transparency and Corruption: Does E-Government Effective to Combat Corruption? - Ismail (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to analyze whether the implementation of e-government in the local government environment in Indonesia is effective in fighting corruption. Through a qualitative approach, the results of this study have revealed the enormous implications of e-government in fighting corruption. The implementation of e- governance in Indonesia aims to improve public services by promoting transparency and accountability in order to prevent corruption. With the application of this system, it is expected that the practices of corruption, collusion and nepotism can be prevented and able to oversee regional planning and development in Indonesia. In practice, the application of electronic-based public services or e-government has not been effective in preventing corruption in local government in Indonesia.